Failure to take X-Ray leading to Misdiagnosis: A Case of Medical Negligence: NCDRC (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
In an alleged medical negligence case of fracture, NCDRC find that the operation for intramedullary nailing of shaft femur was performed without any fault by the qualified Orthopedic Surgeon. However, failure to take appropriate X rays with external rotation of the shaft of the femur to rule out the presence of a sub-clinical occult fracture, may account for pre-operative misdiagnosis. The pre-operative CT scan of the femur neck for all such patients was to be done before intra-medullary nailing of shaft fracture i.e. closed nailing. The CT scan was to be repeated after closed nailing to confirm the condition of the femoral neck, unless a fracture was seen on a plain film or during intra-operative fluoroscopy. If the fracture of neck femur is suspected / evident, then in one sitting both the surgeries for fracture neck and the shaft of femur shall be performed [Para 15]. Having regard to the settled law that an error of judgment/failure to make diagnosis of a complicated condition by itself does not amount to negligence, but it can be said that missing fracture neck femur which normally is missed in 50% cases, is an act of negligence [Para 16]. NCDRC observed that thus, the doctor would be liable only where the conduct falls below the standards of a reasonably competent practitioner in the field [Para 25]. The District Forum awarded Rs. 5.0 lac; whereas the State Commission reduced the award to Rs. 2.5 lac. NCDRC disagreed with the view taken by the State Commission to reduce the quantum of compensation, that there was limited deficiency and negligence from the OP No. 1. NCDRC observed that it is to note that after the treatment, subsequently, the Complainant underwent operation twice in Hedgewar Sansthan at Delhi but his physical condition did not improve. The doctors informed him about no possibility of complete cure in the future. He was the sole earning member in the family. The Complainant had been suffering since the year 2003 and considering the loss of earning capacity and future prospects, in NCDRC view, the compensation of Rs. 5.0 lac is just and fair. Compensation claimed was a total amount of Rs. 1697800/-.
Keywords: Compensation; Medical negligence; Medical negligence Duty; Medical negligence Duty Second opinion; Expert opinion; Medical literature